Cardiac and Vascular Remodeling After 6 Months of Therapy With Sacubitril/Valsartan: Mechanistic Insights From Advanced Echocardiographic Analysis - Monosilio, Sara; Filomena, Domenico; Luongo, Federico; Sannino, Michele; Cimino, Sara; Neccia, Matteo; Mariani, Marco Valerio; Birtolo, Lucia Ilaria; Benedetti, Giulia; Tonti, Giovanni; Pedrizzetti, Gianni; Vizza, Carmine Dario; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background Effects of Sacubitril/Valsartan (S/V) on left ventricular (LV) mechanics and ventricular-arterial coupling in patients with heart failure with reduced ejection fraction (HFrEF) are not completely understood. The aim of this study was to evaluate both cardiac and vascular remodeling in a group of HFrEF patients undergoing S/V therapy. Methods Fifty HFrEF patients eligible to start a therapy with S/V were enrolled. Echocardiographic evaluation was performed at baseline and after 6 months of follow-up (FU). Beside standard evaluation, including global longitudinal strain (GLS), estimated hemodynamic forces (HDFs) and non-invasive pressure-volume curves (PV loop) were assessed using dedicated softwares. HDFs were evaluated over the entire cardiac cycle, in systole and diastole, both in apex to base (A-B) and latero-septal (L-S) directions. The distribution of LV HDFs was evaluated by L-S over A-B HDFs ratio (L-S/A-B HDFs ratio). Parameters derived from estimated PV loop curves were left ventricular end-systolic elastance (Ees), arterial elastance (Ea), and ventricular-arterial coupling (VAC). Results At 6 months of FU indexed left ventricular end-diastolic and end-systolic volumes decreased (EDVi: 101 ± 28 mL vs. 86 ± 30 mL, p < 0.001; ESVi: 72 ± 23 mL vs. 55 ± 24 mL, p < 0.001), ejection fraction and GLS significantly improved (EF: 29 ± 6% vs. 37 ± 7%, p < 0.001; GLS: −9 ± 3% vs. −13 ± 4%, p < 0.001). A reduction of Ea (2.11 ± 0.91 mmHg/mL vs. 1.72 ± 0.44 mmHg/mL, p = 0.008) and an improvement of Ees (1.01 ± 0.37 mmHg/mL vs. 1.35 ± 0.6 mmHg/mL, p < 0.001) and VAC (2.3 ± 1.1 vs. 1.5 ± 0.7, p < 0.001) were observed. Re-alignment of HDFs occurred, with a reduction of diastolic L-S/A-B HDFs ratio [23 (20–35)% vs. 20 (11–28) %, p < 0.001]. Conclusion S/V therapy leads to a complex phenomenon of reverse remodeling involving increased myocardial contractility, HDFs distribution improvement, and afterload reduction.